The PERLOCUTIONARY SPEECH ACTS ON NEWS TEXT OF THE NIRINA ZUBIR LAND MAFIA: CRITICAL DISCOURSE ANALYSIS STUDY - Widyaningrum, Winda; Rasyid, Yumna; Anwar, Miftahulkhairah (IJLECR (International Journal of Language Education and Cultural Review), 2021)
The purpose of this study is to describe the classification of perlocutionary speech acts that can be found in the news text of the Nirina Zubir land mafia case. This methodology uses descriptive qualitative research techniques and text analysis techniques in the data collection process. The author hopes that this study can provide practical and theoretical advantages. Theoretically, this research is expected to contribute knowledge in the realm of pragmatics, especially on the function of perlocutionary speech acts to support the development of pragmatics. Then practically, the author hopes that this research can help readers and the public in understanding the form of perlocutionary speech acts in a news text.